Articulación entre la educación media y la educación superior: una experiencia significativa en la FESAD - Romero Agudelo, Luz Mayelly (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present paper describes the significant experience of the process developed by the University Pedagogical and Technological of Colombia in the implementa- tion of the Articulation Model focused on the implementation of programs by the propaedeutic cycles and the Competence training approach between middle and high school. Higher education within the framework of the agreement between the secretary of department education of Boyacá and the UPTC; it shows the institu- tional commitment that the University has had in the design and development of academic programs based on the contemporary demands and the requirements of the productive sector, as well as the pertinence and the social projection that characterize the supply of programs.